2015
DOI: 10.3390/rs71215824
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bias Correction Method for Soil Moisture and Ocean Salinity (SMOS) Soil Moisture: Retrieval Ensembles

Abstract: Bias correction is a very important pre-processing step in satellite data assimilation analysis, as data assimilation itself cannot circumvent satellite biases. We introduce a retrieval algorithm-specific and spatially heterogeneous Instantaneous Field of View (IFOV) bias correction method for Soil Moisture and Ocean Salinity (SMOS) soil moisture. To the best of our knowledge, this is the first paper to present the probabilistic presentation of SMOS soil moisture using retrieval ensembles. We illustrate that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…However, recent studies showed that a small ensemble size at 12-20 is sufficient to provide the optimal estimates [52]. If perturbing different error sources including land surface heterogeneity, meteorological event, satellite measurement, and parameter inversion errors with the same ensemble size, the resultant ensembles indicate a different quantitative measure of retrieval errors.…”
Section: The Concept and Type Of Retrieval Ensemblesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, recent studies showed that a small ensemble size at 12-20 is sufficient to provide the optimal estimates [52]. If perturbing different error sources including land surface heterogeneity, meteorological event, satellite measurement, and parameter inversion errors with the same ensemble size, the resultant ensembles indicate a different quantitative measure of retrieval errors.…”
Section: The Concept and Type Of Retrieval Ensemblesmentioning
confidence: 99%
“…On the other hand, CDF matching in Figure 5 increased the RMSEs of the original SMOS soil moisture, as CDF matching shifted the original SMOS soil moisture towards reference data exposed to their own intrinsic errors (i.e., the lowest limit of soil moisture is set at wilting point for calculating bare soil evaporation so that model did not appropriately simulate soils in extremely dry conditions drier than the wilting point [106]. Figure 5 shows that the retrieval ensemble mean corrected footprint scale wet biases of the SMOS soil moisture in semi-arid region [52]. Ensembles were generated from a random perturbation of brightness temperature with an ensemble size of 12.…”
Section: Bias Correctionmentioning
confidence: 99%
See 3 more Smart Citations